Analisis Pengaruh Content Marketing Dan Electronic Word of Mouth (E-WoM) Terhadap Keputusan Pembelian Mahasiswa STIE Petra Bitung Pada Media Sosial Tik-Tok - Dumgair, Putra Petra (Universitas Pahlawan Tuanku Tambusai, 2024)
Recent developments in the business world have made it increasingly convenient for consumers to shop online through social media. When shopping, students are drawn to engaging TikTok content and positive electronic word-of-mouth (e-WOM) from previous buyers, sparking their interest in products marketed with captivating short videos. They also browse through reviews on the latest TikTok platform, leading students at STIE Petra Bitung to decide to purchase these products. This research adopts a quantitative approach using purposive sampling (non-probability sampling), where the entire population is considered as the sample, with 87 respondents. Data collection methods include observation to gain a general overview of the object and questionnaires as the measuring tool. The analysis method employed is multiple linear regression analysis, and data management is conducted using SPSS 29. Analytical techniques involve validity testing, reliability testing, classic assumption testing, multiple linear regression testing, and hypothesis testing. The research findings indicate that content marketing (X1) and electronic word-of-mouth (X2) significantly influence purchase decisions (Y), as evidenced by the t-test values (X1) t-test values (X2) > 1.987 and Sig. values of 0.028 < 0.05, 0.01 < 0.05, respectively. This suggests that the variables X1 and X2 have an impact on the variable Y. Furthermore, the data obtained indicate that the influence of content marketing and electronic word-of-mouth on purchase decisions means that H1, H2, and H3 are accepted in this study.